Perlindungan Hukum terhadap Kesejahteraan Pekerja Pasca Putusan Mahkamah Konstitusi Nomor 168/PUU-XXI/2023 - Sitti Shollawatun Hasanah; Sulistina Sulistina (Lembaga Yasin AlSys, 2025)
The issue of legal protection for workers’ welfare has become increasingly relevant, particularly following the Constitutional Court Decision No. 168/PUU-XXI/2023, which addresses legal uncertainty arising from the enactment of the Job Creation Law (Undang-Undang Cipta Kerja). The law has been criticized for neglecting fundamental workers' rights, especially in the regulation of Fixed-Term Employment Agreements (Perjanjian Kerja Waktu Tertentu, PKWT), wage systems, and social security. This study aims to identify the forms and scope of legal protection for workers in Indonesia and to analyze the impact of the Constitutional Court’s decision on the guarantee of workers’ welfare. A normative juridical method was employed, using statutory and conceptual approaches. The findings indicate that legal protection for workers is grounded in the 1945 Constitution, Law No. 13 of 2003 on Manpower, and its implementing regulations. Constitutional Court Decision No. 168/PUU-XXI/2023 reaffirms the importance of registering PKWT as a form of legal recognition of employment relationships, limits the maximum duration of fixed-term contracts to five years, and strengthens the protection of workers’ rights, including fair wages, social security, and just and humane working conditions. In conclusion, this decision provides stronger legal certainty in safeguarding workers’ welfare and serves as a crucial instrument in maintaining balanced industrial relations in Indonesia.